LINKING MARKETING AND HUMAN RESOURCES RECRUITMENT TO OBTAIN ORGANIZATIONAL EFFICIENCY - Nicoleta Valentina FLOREA (Management & Marketing)
In times of rapid change and technical change, in a complex and dynamic environment, organizations must strive for superiority, in order to survive and to serve the clients who want more quality and lower price. Corporate leaders and human resources strategists have to take up this challenge of changing work attitudes across the organization. This involves guiding, leading, enabling and motivating people. This article is looking at aligning marketing with recruitment efforts, to obtain organizational performance. Anticipating customers’ needs, the organization develop specific plans of recruitment, selection and retention of those candidates who satisfy these needs at the highest level. Only anticipating and retaining those “right people at the right time”, an organization may obtain success into a global, dynamic and changing environment.